2018
DOI: 10.1016/j.ijcard.2017.06.033
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between atrial fibrillation and heart failure on long-term mortality and length of stay: Insights from the, United Kingdom ACALM registry

Abstract: Patients with HF in AF are at a greater risk of mortality and longer hospital stay compared to patients without the combination. New-onset AF or HF is associated with significantly worse prognosis than long-standing disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 38 publications
2
28
0
1
Order By: Relevance
“…We explored thirteen candidate predictors for their contributions to the total LOS. All pre-selected risk factors and their cutoffs were chosen based on previous studies which addressed their association with prolonged LOS or mortality: age > 65 years [ 20 ], male gender [ 21 ], chronic kidney disease [ 10 ], ischemic heart disease [ 10 ], diabetes mellitus [ 10 ], atrial fibrillation [ 22 ], NYHA functional class III/IV [ 8 ], systolic blood pressure < 100 or > 140 [ 23 ], respiratory rate > 24 per minute [ 24 ], ProBNP ≥ 1800 pg/mL [ 17 ], serum sodium < 135 mmol/L [ 25 ], hemoglobin < 10 g/dL [ 26 ], and serum albumin < 3.5 g/dL [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…We explored thirteen candidate predictors for their contributions to the total LOS. All pre-selected risk factors and their cutoffs were chosen based on previous studies which addressed their association with prolonged LOS or mortality: age > 65 years [ 20 ], male gender [ 21 ], chronic kidney disease [ 10 ], ischemic heart disease [ 10 ], diabetes mellitus [ 10 ], atrial fibrillation [ 22 ], NYHA functional class III/IV [ 8 ], systolic blood pressure < 100 or > 140 [ 23 ], respiratory rate > 24 per minute [ 24 ], ProBNP ≥ 1800 pg/mL [ 17 ], serum sodium < 135 mmol/L [ 25 ], hemoglobin < 10 g/dL [ 26 ], and serum albumin < 3.5 g/dL [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…New-onset AF or HF was associated with significantly worse prognosis than longstanding disease. 11 Another study found that higher admission heart rate (HR) was independently associated with worse outcomes in patients admitted for HF, both for those in sinus rhythm and AF. 12 In the randomised Beta-blocker Evaluation of Survival Trial (BEST), patients with HFrEF who developed new-onset AF were found to exhibit a two-fold increase in mortality and a 4.5-fold increase in all-cause or HF hospitalization, compared with patients who did not develop AF.…”
Section: Prognosis and Outcomes In New Onset And Pre-existing Afmentioning
confidence: 99%
“…AF is a worldwide epidemic involving nearly 50% of patients with advanced HF [6]. Some meta-analyses have shown that coexistence of HF and AF is associated with higher all-cause mortality over time compared with those with single disease, and the worse prognosis is independent from the severity of systolic dysfunction [7-10]. In detail, the original Framingham Heart Study showed that in 1,737 individuals, 37% of de novo AF was in patients with HF, while 57% of de novo HF was in patients with AF [11].…”
Section: Af In Advanced Hfmentioning
confidence: 99%